How Germany shouldered the fiscal burden of the unification - Alfred Boss (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
In the process of the German unification and especially after the formal unification in October 1990, Eastern Germany was supported by West Germany by a lot of measures. The main purposes were to improve the infrastructure, to stimulate private investment and to alleviate the adjustment process for the population by transfers to private households. The paper describes the measures in some detail. Many of these were decided upon in an ad hoc manner, in some cases experience (partly from the period of reconstruction in West Germany after World War II) was available. The methods of financing are described, too. Emphasis is laid on the policy in the field of social insurance. Finally, it is tried to draw some conclusions which might be helpful in case of a unification of South and North Korea.
Keywords: H59; H79; 330; intergovernmental relations; debt; social security; Finanzpolitik; Öffentlicher Transfer; Sozialversicherung; Sozialtransfer; Öffentliche Schulden; Öffentlicher Haushalt; Nationale Einheit; Deutschland; Neue Bundesländer